2012
DOI: 10.1074/jbc.m111.311316
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cysteine Residues and Disulfide Bonds in the Activity of a Legume Root Nodule-specific, Cysteine-rich Peptide

Abstract: Background: Legume antimicrobial peptides (AMPs) mediate Sinorhizobium meliloti bacteroid differentiation. Results: Cysteine replacements and disulfide bond modifications influence the antimicrobial activity of a legume AMP and its ability to mediate S. meliloti bacteroid differentiation. Conclusion: Specific changes to legume AMPs influence their activity against S. meliloti. Significance: Understanding the relationship of AMPs in S. meliloti bacteroid differentiation is fundamental for nitrogen fixation and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
65
1
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 80 publications
(70 citation statements)
references
References 28 publications
2
65
1
1
Order By: Relevance
“…It has been suggested that this chemical and structural diversity impacts peptide activity, as found in other families of small disulfide-linked peptides that exhibit rich chemical and structural diversity (4,49). Indeed, experiments on modified versions of the NCR247 peptide indicated that the presence and order of disulfide bonds between cysteine residues significantly influences peptide antimicrobial activity (50). It has been proposed that NCR peptides (i) alter the S. meliloti cell cycle and metabolism to achieve a more efficient symbiosis (4), (ii) sanction non-nitrogen-fixing rhizobia (4), (iii) kill senescent bacteroids so that their nutrients can be absorbed by the plant (4,48), and (iv) serve as signals to the plant (48).…”
Section: Discussionmentioning
confidence: 99%
“…It has been suggested that this chemical and structural diversity impacts peptide activity, as found in other families of small disulfide-linked peptides that exhibit rich chemical and structural diversity (4,49). Indeed, experiments on modified versions of the NCR247 peptide indicated that the presence and order of disulfide bonds between cysteine residues significantly influences peptide antimicrobial activity (50). It has been proposed that NCR peptides (i) alter the S. meliloti cell cycle and metabolism to achieve a more efficient symbiosis (4), (ii) sanction non-nitrogen-fixing rhizobia (4), (iii) kill senescent bacteroids so that their nutrients can be absorbed by the plant (4,48), and (iv) serve as signals to the plant (48).…”
Section: Discussionmentioning
confidence: 99%
“…Cys is a very important metabolite not only as a proteinogenic amino acid, but also by its function as a precursor of essential biomolecules. In proteins, the thiol group of Cys, susceptible of oxidation to render disulfide bridges, stabilizes the tertiary and quaternary protein structures and, consequently, determines protein function (Haag et al 2012 ), and often located in enzyme active sites are essential for catalysis (Richau et al 2012 ). Moreover, the reversible conversion between free thiols groups and disulfide bridges is the basis of protein redox regulation (Buchanan and Balmer 2005 ).…”
Section: Introductionmentioning
confidence: 99%
“…Its disulfide bridge plays important roles in its biological activities. Similarly, Haag et al (19) found that the nodule-specific cysteinerich peptide (NCR247) had decreased activity against Sinorhizobium meliloti when cysteines were substituted for serines or the S-S bridges were changed from cysteines 1-2 and 3-4 to cysteines 1-3 and 2-4.…”
Section: Discussionmentioning
confidence: 99%